THE EFFECT OF PRICE DISCOUNTS AND PROMOTION ON PURCHASING WITH WORD OF MOUTH AS A MODERATING VARIABLE - Frans Sudirjo; Fitri Novilia; Hadiansyah Ma’sum; Helmina br. Ginting; Rudi Kurniawan (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract Price discounts are one of the factors that researchers believe can influence consumer purchasing decisions and are even the main factor that consumers take into account, especially for products that are not too much different in quality. Apart from price cuts, researchers also believe that promotional factors can also influence purchasing decisions due to the expanding market share and the increasing number of potential consumers who know about a product. Therefore, this research aims to analyze the effect of price discounts on purchasing decisions. Different from previous research, this research adds the Word of Mouth variable as a moderating variable. This research is qualitative research with an explanatory approach. The data used in this research is primary data that researchers obtained from the questionnaire method of 300 Shopee application users consisting of 150 sellers and 150 buyers. The questionnaire is in the form of multiple choices containing the words strongly agree-strongly disagree. These data were analyzed using the smart PLS 4.O method. Keywords : Price Discounts, Promotion, Purchasing, Word of Mouth